Non-dependence of nuclear decay rates of 123I and 99mTc on Earth-Sun distance. (February 2018) - Borrello, Joseph A.; Wuosmaa, Alan; Watts, Mark
Abstract: Recently published studies have suggested an annual fluctuation of the decay rate of several radionuclides, in particular 32 Si and 226 Ra. Variation of solar neutrino flux caused by variation of Earth-Sun distance has been proposed as the mechanism of this fluctuation. In this study we prospectively look at two radionuclides which have not previously been studied for annual variation, 123 I and 99 m Tc. Half-lives of samples of these radionuclides were measured approximately weekly and semiweekly respectively over a period of 2 years. Spectral analysis using the Lomb-Scargle method demonstrated no significant periodicity, and in particular, no evidence for a period of 1 year. Abstract : Highlights: Recent studies suggest an annual variation in decay rate of some radionuclides. The existence of this effect is controversial. We prospectively look for this effect in two previously unstudied radionuclides. We find no evidence of this effect in 123 I or 99m Tc. We exclude annual periodicity at the magnitude found in previous studies.